Pendampingan Pengembangan Materi Ajar PAI Moderasi Beragama Di TPA Taman Bocah Permata Hati Sleman - Nugroho, Taufik; Nasrudin, Muhammad; Fadilah, Fadilah; Syavicky, Ahmad Reihan; Yurniati, Yurniati (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
This article is a report on community service funded by LPPM UCY 2023/2024. The background to this community service problem is that there are strong symptoms of widespread Islamic religious intolerance in DIY, where this is thought to have become endemic in formal Islamic educational institutions, both state and private, from PAUD to Higher Education. Therefore, this community service tries to: 1. Answer real problems in the field in the form of activities to strengthen religious moderation material with the hope that symptoms of religious intolerance do not spread in all directions without control. 2. This activity limits itself to providing assistance in strengthening religious moderation material at Taman Bocah Permata Hati Banyuraden, Gamping, Sleman. The method used in this activity is Focus Group Discussion (FGD) regarding: 1. Exploring the reality of PAI learning at this institution. 2. Explore problems that arise in learning and their practical implications. 3. Brain storming problem solving 4. Conclusion. The results of this community service can be reported as follows: the reality of PAI learning at Taman Bocah Permata Hati TPA does not yet see the importance of religious tolerance, the main goal of PAI is to build faith and devotion to Allah SWT, be loyal to the teachings of Islam and fight in the path of Allah SWT or jihad. sabilillah. Meanwhile other Islamic teachings such as; tasammuh, equality without discrimination is not considered important or has not become PAI's main need. The hope is that through PAI students will become tolerant in religion; flexible in relationships, non-discriminatory in his actions and equal in viewing fellow members of society. The birth of students who are moderate in religion must be supported by PAI teaching materials and teachers who are skilled in instilling the value of religious moderation in students. Therefore, there is a need for assistance and strengthening of religious moderation PAI teaching materials. Suggestions to managers to expand teachers' religious moderation perspectives, sending teachers to religious moderation training.